Building Critical Thinking Skills is the Basis Of Improving Intellectual Ability. - Senior teacher M. J. Makhammatova (Periodica Journal, 2023)
This article talks about pedagogical considerations aimed at forming critical thinking skills, the essence of critical thinking. Ways to improve intellectual ability through the formation of critical thinking skills are widely described.
Keywords: critical thinking; reflective thinking; thinking about thinking, conceptualization; cognitive